Adversarial Principle and Principle of Equality of Arms as a Subject of Adversarial Type of Criminal Proceeding - SADIEV, Gakharman Sanan-Ogly (Journal of Advanced Research in Law and Economics; Vol 7 No 4 (2016): JARLE, Volume VII, Issue 4(18), Summer 2016, 2016)
The article concerns adversarial principle and principle of equality of arms as a subject of adversarial type of criminal proceedings. Adversariality, being complex legal phenomenon, also has its structure and system of features that includes: (1) functions of prosecution, defense and resolution of criminal cases are separated from each other and cannot be imposed on the same authority or the same official; (2) court is not an authority of persecution, it acts neither on the part of prosecution, nor on the part of defense. Court provides necessary conditions for parties’ execution of their procedural obligations and exercise of their granted rights. The prosecution and the defense are of equal rights to the court. The subject matter of adversarial system implies: presence of equal parties; separation of main procedural functions; presence of impartial arbitrator – the court that is aimed at resolution of procedural conflicts of parties. Exclusion of any of denoted elements would not only make the subject of considered principle incomplete, but also put in question the very possibility of its existence. So, modern criminal court is an active participator of proving procedure in all its aspects playing operational and control role in the present sphere of criminal procedural activity.